2015
DOI: 10.3109/0142159x.2014.1001730
|View full text |Cite
|
Sign up to set email alerts
|

Twelve tips for addressing medical student and resident physician lapses in professionalism

Abstract: Medical educators have gained significant ground in the practical and scholarly approach to professionalism. When a lapse occurs, thoughtful remediation to address the underlying issue can have a positive impact on medical students and resident physicians, while failure to address lapses, or to do so ineffectively, can have long-term consequences for learners and potentially patients. Despite these high stakes, educators are often hesitant to address lapses in professionalism, possibly due to a lack of time an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 44 publications
(43 reference statements)
0
29
0
Order By: Relevance
“…Teachers are indeed known to experience barriers in referring students. 31 - 33 Unprofessional behaviour might be underreported for reasons similar to those of clinical lecturers who do not fail students. Dudek et al identified four major barriers to failing trainees: ‘(1) lack of documentation, (2) lack of knowledge of what to specifically document, (3) anticipating an appeal process, and (4) lack of remediation options’.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers are indeed known to experience barriers in referring students. 31 - 33 Unprofessional behaviour might be underreported for reasons similar to those of clinical lecturers who do not fail students. Dudek et al identified four major barriers to failing trainees: ‘(1) lack of documentation, (2) lack of knowledge of what to specifically document, (3) anticipating an appeal process, and (4) lack of remediation options’.…”
Section: Discussionmentioning
confidence: 99%
“…This theory encompasses that a student's ultimate behaviour is influenced by intentions and beliefs about the behaviour and its outcomes, the subjective norm, and the perceived behavioural control. Another (Howe et al 2010) Stress the effect of students' unprofessional behaviour on future patient-safety (Howe et al 2010;Yepes-Rios et al 2016;Wong et al 2017) Emphasize role modeling of responding to unprofessionalism to educators (Rougas et al 2015) Inform teachers about policies (Rougas et al 2015) Offer the possibility to educators to discuss their experiences with colleagues and get mutual support (e.g. in teacher communities The student displays an accidental professionalism lapse and is capable to prevent future professionalism lapses with help from regular teachers in the medical curriculum.…”
Section: Explore and Understandmentioning
confidence: 99%
“…For most students, this approach is sufficient to prevent future unprofessional behaviour. Furthermore, these conversations can yield important information about (hidden) organizational and contextual causes for students' unprofessional behaviour that can be fed back into the organization (Lesser et al 2010;Rougas et al 2015).…”
Section: Explore and Understandmentioning
confidence: 99%
“…19 Limited time to identify and managing unprofessionalism issues can also lead to a lack of uncertainty for tutors in reporting incidences, either formally or informally. 23 This was highlighted in relation to con dence in dealing with a professionalism issue. It has been reported that some faculty see formal professionalism curricula as an attempt to "force all students into the straightjacket of political correctness" 4 and this may explain some of the reluctance of our tutors to follow a formal route when intervening.…”
Section: Discussionmentioning
confidence: 99%